2016
DOI: 10.1177/1932296815626726
|View full text |Cite
|
Sign up to set email alerts
|

Polytetrafluoroethylene Ingestion as a Way to Increase Food Volume and Hence Satiety Without Increasing Calorie Content

Abstract: Since satiety is largely due to stretch of the stomach and people tend to eat a consistent weight of food, increasing food volume and mass increases satiety. This can be achieved without increasing the calories of food by mixing food with a material that cannot be metabolized. Such a material should be inert, safe, resistant to stomach acid, lack taste, available in powder form, smooth, resistant to heat, and cost effective. Polytetrafluoroethylene (PTFE) is an ideal substance for this purpose. It is a soft pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Polytetrafluoroethylene (PTFE), popularly known as the brand name Teflon ® , is a material broadly used in many industrial sectors and is also called “King of Plastics” [ 24 , 25 , 26 , 27 , 28 ]. PTFE is well known for its good chemical, thermal, electrical stability, and low friction that draw interests of many researchers [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polytetrafluoroethylene (PTFE), popularly known as the brand name Teflon ® , is a material broadly used in many industrial sectors and is also called “King of Plastics” [ 24 , 25 , 26 , 27 , 28 ]. PTFE is well known for its good chemical, thermal, electrical stability, and low friction that draw interests of many researchers [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTFE itself is considered inert, with low health or environmental concern; 41,42 even ingestion up to 25% of the diet is not considered a health risk. 43 The heat treatment partially softens the PP microfibers, which promotes nano- 1b compares the physical morphology of nonwoven textile before (i) and after (ii) surface treatment with images from scanning electron microscopy (SEM). Untreated samples are composed of thermally bonded PP microfibers approximately 2−8 μm in diameter (Figure 1b-i).…”
Section: Resultsmentioning
confidence: 99%
“…The coating solution is drop cast onto both sides of the nonwoven textile (Figure a-i), followed by a heat treatment to evaporate the solvent and thermally sinter PTFE nanoparticles to nonwoven PP microfibers (Figure a-ii). PTFE itself is considered inert, with low health or environmental concern; , even ingestion up to 25% of the diet is not considered a health risk . The heat treatment partially softens the PP microfibers, which promotes nanoparticle impregnation without causing any pyrolysis of PTFE.…”
Section: Resultsmentioning
confidence: 99%
“…It is resistant to gastric juice and is extremely stable. In confirmation of the inertness of this polymer, Naftalovich and colleagues [49] have experimentally shown that rats fed a diet containing 25% PTFE for 90 days showed no signs of toxicity. Furthermore, based on these results, they have suggested that this polymer could be used for food supplementation to significantly improve satiety and reduce caloric intake in humans.…”
Section: Resultsmentioning
confidence: 93%